CHANGES IN THE LEVELS OF ANGIOTENSIN II, ALDOSTERONE, AND FIBROBLAST GROWTH FACTOR IN PATIENTS WITH RHEUMATOID ARTHRITIS IN RELATION TO CLINICAL FEATURES - E. B. Komarova; B. A. Rebrov (Научно-практическая ревматология, 2016)
Angiotensin II, aldosterone, and fibroblast growth factor (FGF) stimulate neoangiogenesis, fibroblast proliferation, and elaboration of proinflammatory cytokines, which in turn contributes to increased pannus mass and the development of joint tissue destruction in rheumatoid arthritis (RA).Objective: to establish the specific features of changes in the blood levels of angiotensin II, aldosterone, and FGF in patients with RA in relation to the duration and severity of the disease.Subjects and methods. Examinations were made in 194 patients diagnosed with RA without comorbidity; the patients’ mean age was 47.7±10.2 years; the disease duration was 3.82±3.43 years. DAS28 scores for RA were calculated based on C-reactive protein levels. An enzyme immunoassay was used to determine the serum levels of anti-cyclic citrullinated peptide antibodies (ACCPA), angiotensin II, aldosterone, and FGF.Results and discussion. All the examinees were ascertained to have increases in the concentration of angiotensin II and aldosterone in blood by twice and in that of FGF by 2.5 times compared to the controls (p < 0.05). In patients with a RA duration of < 2 years, the blood level of angiotensin II was 25% higher than in those with a RA duration of > 5 years and the concentrations of aldosterone and FGF in patients with long-term RA were twice as high as in those with early RA. In patients with high RA activity, the blood level of angiotensin II was 1.5-fold higher than in those with low and moderate disease activity (p < 0.05). In patients with a high blood ACCPA level, the concentrations of angiotensin II, aldosterone, and FGF were 20, 30, and 25%, respectively, higher than in those with low ACCPA levels. The correlation of DAS28 with blood angiotensin II levels increased with enhanced RA activity. The high aldosterone and FGF values in RA patients are associated with the progression of joint radiographic changes.